2013
DOI: 10.1007/s00056-012-0123-y
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of bovine and human teeth exposed to thermocycling for microleakage under bonded metal brackets

Abstract: Immediately after bonding, less microleakage was observed around the base of metal brackets on human than bovine teeth. These marginal gaps were, however, superficial in both groups, none of them involving deep penetration of dye under the bracket base.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 31 publications
0
9
0
Order By: Relevance
“…[16][17][18][19] In the recent study, more than half the brackets of group A and almost all brackets of group B showed discoloration of some kind at any bracket edge. Although the protocol was used before, 20 showing a lower incidence of microleakages for conventional adhesive-bracket combination, this might be because in this study, only a yes/no decision was obtained. For further studies, the sensitivity of this specific testing procedure should be increased.…”
Section: Discussionmentioning
confidence: 98%
“…[16][17][18][19] In the recent study, more than half the brackets of group A and almost all brackets of group B showed discoloration of some kind at any bracket edge. Although the protocol was used before, 20 showing a lower incidence of microleakages for conventional adhesive-bracket combination, this might be because in this study, only a yes/no decision was obtained. For further studies, the sensitivity of this specific testing procedure should be increased.…”
Section: Discussionmentioning
confidence: 98%
“…This repeated expansion and contraction at different coefficients results in fluids being sucked in and pushed out at the margins of the bracket. P (23) P In the present study, the dye penetration method was chosen to assess microleakage as it has been used in most of the previous orthodontic studies.P (6,9,24) P In general, study by Arhun and ArmanP (25) P , concluded that metal brackets contract and expand more than ceramic brackets producing microgaps between the bracket and the adhesive system causing leakage of oral fluids and bacteria beneath the brackets, leading to the formation of white spot lesion.…”
Section: Discussionmentioning
confidence: 99%
“…So, bracket designs with different surface characteristics create different bonding environments. (9) Recently, new generations of orthodontic adhesives were presented. The 5th generation of bonding systems is similar in principle to the 4th generation materials, except that it has been designed to require fewer stages in their placement in an attempt to reduce technique sensitivity and treatment time.…”
Section: Issn:1812-1217mentioning
confidence: 99%
See 1 more Smart Citation
“…All the teeth were then etched for 30 s with 37% phosphoric acid solution (Ormco Etching Solution, Ormco, Glendora, California) followed by 5 s of water rinsing and 5 s of air drying. [11]…”
Section: Methodsmentioning
confidence: 99%